Impressão 3D na produção de materiais para o laboratório de Física: uma possibilidade - Abreu, Reginaldo de (Universidade Federal de São Carlos, 2025)
There is a growing concern that new generations are becoming increasingly less inclined toward scientific careers and more apathetic in school activities. Driven by this context, this study aims to shed light on the possibility of increasing students' interest in Physics through experimental activities. Based on the assumption that there is a lack of equipment in high school physics laboratories and that students are avid consumers of technology, this research proposes using 3D printing to produce instructional materials for physics laboratories while also captivating students through a manufacturing technology that is widely discussed but not well understood. To assess this possibility, a set of laboratory materials was designed and 3D-printed by the author and subsequently employed in a seven-week course with eight high school students at a private school in the state of São Paulo, Brazil. The activities covered Dynamics (determination of gravitational acceleration and acceleration in pulley systems) and Statics (conditions of equilibrium in systems with concurrent forces in different configurations). Students were responsible for assembling the equipment, making theoretical predictions, experimentally obtaining the expected quantities, and comparing the results while identifying possible sources of discrepancy. At the end of the course, semi-structured interviews were conducted with some students, which revealed both motivational and methodological impacts of 3D printing in Physics teaching: on the one hand, fostering curiosity in the technological field by demonstrating that the equipment was designed and manufactured within the school itself - thus highlighting the feasibility of 3D printing for educational and domestic use - and, on the other hand, enabling the implementation of experimental strategies in Physics through low-cost, teacher-designed materials that can also be shared across other areas of knowledge.
3D printing in the development of materials for the Physics laboratory: a feasible approach
Keywords: Ensino de Física; Manufatura Aditiva; Prototipagem; Material Didático; Polias; Mesa de Forças; Physics Teaching; Additive Manufacturing; Prototyping; Instructional Material; Pulleys; Force Table; CIENCIAS EXATAS E DA TERRA::FISICA; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade; 12. Consumo e Produção Responsáveis; 9. Indústria, Inovação e Infraestrutura